Las hormigas Ecitoninae (Hymenoptera: Formicidae) de Morelos, México - Quiroz Robledo, Luis N. (2006)
Abstract. The Ecitoninae ants (Hymenoptera: Formicidae) from Morelos, México. To produce an inventoryof the Ecitoninae ants from Morelos State (south central Mexico), we used direct capture and pit-fall traps.Occasionally, males were also collected near artificial light sources. Fifteen species were found: Labidus coecus,L. praedator s. str., Neivamyrmex agilis, N. cornutus, N. fallax, N. graciellae, N. impudens, N. macropterus, N.melanocephalus, N. nigrescens, N. opacithorax, N. pauxilus, N. sumichrasti, N. swainsoni and Nomamyrmexesenbecki mordax. Twelve of these species are new records for the state. The most abundant species were L.coecus, N. melanocephalus, N. nigrescens and N. esenbecki mordax. The distribution of the species in the state,flight dates of males for some species, and a key for the identification of workers and males are included. Oneadditional species (N. fuscipennis), collected by other authors in Morelos but not by us, is also included in thekey.